New Types of the Regional Atlases (On the Example of the Kraków Voivodeship Computer Atlas) - Trafas, Kazimierz (LIBER Quarterly: The Journal of the Association of European Research Libraries, 1999)
When new technologies were introduced in cartography, and especially computer technologies and Geographic Information Systems (GIS), maps and atlases began to be used in a different way. Passive forms (reviewing, overlap drawing) have been replaced by more active forms (generating new information, visualisation and animation of the spatial data). Thus cartographic collections in libraries are to play a different role. It is necessary to adjust them to the use of maps existing on electronic media, recorded on disks or CD-ROMs, offering a possibility to scan and print the data. Simple programmes which visualise spatial data should also be available in libraries. In the near future the major role in cartographic collections will be probably played by electronic atlases consisting of aggregated data bases (geographic, statistic and others) composed of many layers and attributes which will be combined according to the user’s needs and thus new maps will be created. The Kraków Voivodeship Computer Atlas (KVCA) which is now being prepared in Kraków is such an electronic atlas. In this paper, the author presents some remarks about this new type of the regional atlas on the basis of experience acquired in preparing of this atlas.